TOWARDS A GUIDE TO PALAEOBIOGEOGRAPHIC CLASSIFICATION - Cecca F.; Westermann G.E.G. (My University, 2003)
The present paper is a report of work completed by the group 'Friends of Paleobiogeography' on the principles of palaeobiogeographic classification and nomenclature of palaeobiogeographic units (biochoremas). These principles are intended to complement those of neobiogeography and are aimed at enhancing palaeobiogeography in general by a simplified and standardised terminology.
Keywords: PALAEOBIOGEOGRAPHY; PALAEOBIOGEOGRAPHIC UNIT; BIOCHORE; BIOCHOREMA